"They say/I say" : the moves that matter in academic writing, with readings - Graff, Gerald; Birkenstein, Cathy; Durst, Russel K., 1954- (New York : W.W. Norton & Company, 2015)
They Say / I Say demystifies academic writing by identifying its key rhetorical moves, the most important of which is to summarize what others have said ("they say") to set up one's own argument ("I say"). The book also provides templates to help students make these key moves in their own writing. This version includes readings that demonstrate those moves-and provide stimulating conversations for them to enter. The third edition includes an anthology of over 40 essays on five issues that matter to high school students today.
They say -- Her point is -- As he himself puts it -- Yes, no, okay, but -- And yet -- Skeptics may object -- So what? Who cares -- As a result -- Ain't so/is not -- But don't get me wrong -- He says contends -- I take your point -- IMHO -- What's motivating this writer? -- Analyze this -- Is college the best option? -- Are we in a race against the maince? -- What should we eat? -- What's up with the American dream? -- What's gender got to do with it?
Includes bibliographical references and index.
Keywords: English language -- Rhetoric -- Handbooks, manuals, etc; Persuasion (Rhetoric) -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc; Academic writing -- Handbooks, manuals, etc; College readers